Efficiency in the forward exchange market - an application of co-integration - reply - Lucey, BM (Economic & Social Studies, 1989)
In this issue of the Economic and Social Review, Leddin comments on my recent (1988) paper which examined co-integration as a technique for analysing the efficiency of the forward exchange market. This paper addresses a small number of the interesting points raised in this Comment.
Keywords: Forward exchange; Economics